Pengaruh Kompetensi Sumber Daya Manusia dan Penerapan Sistem Akuntansi Keuangan Daerah terhadap Kualitas Laporan Keuangan Daerah - Saputro, Herbangun Giri; Aditya, Elma Muncar; Indarti, Iin (STIE Widya Manggala, 2025)
The purpose of this study was to determine the influence of human resource competence and the influence of the regional financial accounting system (SAKD) on the quality of regional government financial reports at the Genuk District Office, Semarang. This study uses a comparative causal research design using survey methodology. The data in this study are quantitative, consisting of numeric values. The sample used in this study were 42 employees of the finance department at the Genuk District Office, Semarang. The results of data processing using SPSS 26 can be concluded that it was found that human resource competence has a significant positive effect on the quality of regional financial reports in Genuk District, Semarang City, the application of the regional financial accounting system does not affect the quality of regional financial reports in Genuk District, Semarang City, and human resource competence and the application of the regional financial accounting system simultaneously have a significant effect on the quality of regional financial reports.